Effect of epoxidized palm oil as plasticizer on polyhydroxyalkanoates mechanical behavior - Abdullah, Aida Ashikin; Hassan, Norita (Zes Rokman Resources, 2016)
Most of thermoplastic used nowadays are petroleum based polymer which is from a non-renewable and limited source. Previous researchers has found a thermoplastic polymer polyhydroxyalkanoates (PHA) that exhibit biodegradable properties and produced from renewable materials such as sugar and molasses. However, pure PHA are brittle materials. A modification on the mechanical properties of PHA can be done by introducing plasticizer to the materials. In this study, epoxidized palm oil (EPO) is used as plasticizer to PHA at different percentage loading. PHA with different percentage loading of (EPO) was blend using internal mixer. The mechanical properties of each sample was determine by tensile test. Results shows that stiffness of PHA was improved with 3wt% optimum plasticizer loading.